Penguatan Karakter Sadar Wisata kepada Masyarakat Desa Kamarang Kecamatan Greged, Kabupaten Cirebon, Provinsi Jawa Barat melalui Kegiatan Pelatihan Sadar Wisata - lala siti sahara (Jurnal Abdimas Pariwisata, 2022)
Strengthening Tourism Awareness Characters for the Community of Kamarang Village, Greged District, Cirebon Regency, West Java Province through Tourism Awareness Training Activities. Kamarang Village is located in Greged Subdistrict, Cirebon Regency, West Java Province, the main problems faced by Kamarang Village since becoming a tourist village startup include: lack of public knowledge about the concept of tourism awareness, village tourism potential, infrastructure facilities supporting tourism that are less complete, and not optimal community participation in the management of tourist villages. Strategies that need to be done to overcome these problems one of them is through the strengthening of tourism awareness to the community. Training activities have been carried out in September 2021 to 25 residents of Kamarang Village who are tourism actors (such as: members of tourist conscious groups, community leaders, cultural figures, PKK mothers, and others). Activities are carried out by the delivery of tourism village development materials and tourism awareness. The purpose of this activity is to improve the conscious understanding of tourism for the community as well as increasing skills in the packaging of service products in tourist villages.